Creative Empowerment In Branding And Digital Publication Design To Enhance Sales Of Small Business Products In The Leather Shoe Craft Center Of Cibaduyut - Pertiwi, Annisa Bela; Farid, Rudy; Budiman, Budiman; Firdaus, Muhammad (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
Since the implementation of free trade agreements (AFTA) and ACFTA (Global Trade with China), the development of the leather industry in Cibaduyut Village has experienced a decline in production. Local small and medium enterprises (SMEs) in Cibaduyut Village must adapt to marketing systems that use communication technology. Social media has become an easy and inexpensive way to reach consumers. However, the main issue is that due to the rapid advancement of technology, not all SMEs in the Cibaduyut leather center can adapt quickly. They need to learn extensively and familiarize themselves with using technology (e-commerce). Effective product branding and attractive social media design can also enhance brand awareness, thereby leaving a distinct impression of the product in the public’s mind. According to a Sea Insights survey, 54% of SME respondents are increasingly adaptive in using social media to boost sales (Alika, 2020). E-commerce usage is a growing trend in Indonesia and will continue to evolve, leading to new innovations.